The Current Landscape of US Pediatric Anesthesiologists: Demographic Characteristics and Geographic Distribution. (July 2016) - Muffly, Matthew K.; Muffly, Tyler M.; Weterings, Robbie; Singleton, Mark; Honkanen, Anita
Abstract : BACKGROUND: There is no comprehensive database of pediatric anesthesiologists, their demographic characteristics, or geographic location in the United States. METHODS: We endeavored to create a comprehensive database of pediatric anesthesiologists by merging individuals identified as US pediatric anesthesiologists by the American Board of Anesthesiology, National Provider Identifier registry, Healthgrades.com database, and the Society for Pediatric Anesthesia membership list as of November 5, 2015. Professorial rank was accessed via the Association of American Medical Colleges and other online sources. Descriptive statistics characterized pediatric anesthesiologists' demographics. Pediatric anesthesiologists' locations at the city and state level were geocoded and mapped with the use of ArcGIS Desktop 10.1 mapping software (Redlands, CA). RESULTS: We identified 4048 pediatric anesthesiologists in the United States, which is approximately 8.8% of the physician anesthesiology workforce ( n = 46, 000). The median age of pediatric anesthesiologists was 49 years (interquartile range, 40–57 years), and the majority (56.4%) were men. Approximately two-thirds of identified pediatric anesthesiologists were subspecialty board certified in pediatric anesthesiology, and 33% of pediatric anesthesiologists had an identified academic affiliation. There is substantial heterogeneity in the geographic distribution of pediatric anesthesiologists by state and US Census Division with urban clustering. CONCLUSIONS: This description of pediatric anesthesiologists' demographic characteristics and geographic distribution fills an important gap in our understanding of pediatric anesthesia systems of care. Abstract : Published ahead of print April 5, 2016